Implementasi Tugas Kepala Sekolah Di SMA Negeri I Kabupaten Deiyai Provinsi Papua Tengah - Yulius Pekei; Yulius Mataputun; Cornelius Tanto (Sekolah Tinggi Katolik Touye Paapaa Deiyai, 2024)
The purpose of this study was to analyze the implementation of the duties of the principal of SMA Negeri 1 Deiyai in arousing and stimulating Tendik, equipping school equipment, developing teaching methods, carrying out harmonious cooperation between teachers, developing the quality of teachers' knowledge, fostering cooperative relationships between Tendik, students and parents at SMA Negeri 1 Deiyai, Southeast Papua Province. This research uses a qualitative approach with a descriptive method about the implementation of the duties of the school principal at SMA Negeri 1 Deiyai. The source of the results of interviews with principals, teachers, TU administration and students from SMA Negeri 1 Deiyai. Based on the results of this study indicate that the head of SMA N 1 Deiyai Regency, Central Papua Province has implemented the duties of the principal as follows: 1) Generating and stimulating Tendik in their respective duties both from teaching readiness to grade management responsibilities. Directing and supervising from planning, process to evaluation based on applicable regulations. 2) Equipping school equipment for the smooth teaching-learning process in the classroom The school principal can begin by identifying priority needs and involving subject teachers to discuss the financing program. 3) Develop teaching methods that are in accordance with the demands of the new curriculum affected by the lack of socialization from related agencies